Parenting desires, parenting intentions, and anticipation of stigma upon parenthood among lesbian, bisexual, and heterosexual women in Portugal. Issue 4 (2nd October 2019) - Gato, Jorge; Leal, Daniela; Tasker, Fiona
Abstract: We explored parenting desires, parenting intentions, and anticipation of stigma upon parenthood in a sample of 257 self-identified lesbian, bisexual, and heterosexual childfree women in Portugal. No differences between the groups were observed concerning parenting desires. However, lesbian and bisexual women reported lower intentions to have children than their heterosexual counterparts. Although lesbian women considered themselves to have a higher chance of being victims of social stigma as mothers, this was not associated with their parenting desires. Furthermore, younger lesbian women intended to have children to a greater extent than did older lesbian women; relational status did not relate to lesbian women's parenting intentions, desires, or anticipation of stigma. Overall, this study contributes to knowledge about family formation processes among Portuguese women diverse in sexual identity.